The effect of duration of ownership and time spent together during the day on cat owners' level of understanding of cats' body language - Koseman, Abdurrahman; Seker, Ibrahim; Erez, Abdulsamed; Kosan, Senol (Univ Zulia, Facultad Ciencias Veterinarias, 2024)
The study was conducted to determine the effect of the duration of ownership of cats ( Felis catus) ) and the time spent by the owners with their cats during the day on understanding the body language of cats. Face-to-face survey data from 194 cat owners were used in the study. In the study, the ratios of females who spent 1-5 hours (h), 6-10 h and 11 h or more with their cats was 49.6, 69.4 and 62.5%, respectively; 41.9, 59.2 and 56.2%, respectively; 48.8, 55.1 and 50.0%, respectively; and 45.0, 55.1 and 43.7%, respectively, of those aged 20 years and younger. In this study, it was determined that cat owners understood 6 of the 20 images of cat body language with 55.2% or more accuracy and 14 of them with 42.8% or less accuracy. In the study, it was determined that those who understood cat body language at the highest rate were female, associate degree and bachelor's degree graduates, 21-40 years old, and those who spent 1-5 h a day with their cats. As a result, it was determined that it is not sufficient for cat owners to understand their cats' body language correctly only if they have owned their cats for a long time and spend long periods of time together during the day. This is due to the fact that there are many factors affecting the behavior of cats and individual differences. It is recommended that cat owners learn cat body language to better understand their cats.
El efecto de la duración de la propiedad y el tiempo que pasan juntos durante el día en el nivel de comprensión del lenguaje corporal de los gatos por parte de los dueños de gatos
Keywords: Cat; cat behavior; cat body language; cat owner; consciousness